Recreation of the “Olonkho Style” in Russian in Translations of the Epic Works of P. A. Oyunsky - Vasil’eva, Akulina Aleksandrovna (Journal of History Culture and Art Research, 2018)
The highest form of the folklore of every nation is the epic which expressive means are unique in relation to the artistic word of other nations and are common for all the oral and literary artistic creativity of the nation which wrote the epic. Therefore, the article's comparative analysis of the translation equivalents of the linguistic means which form the elevated “olonkho style” in Russian is conducted on the basis of the works of one of the founders of Yakut literature, Platon Oyunsky, and has the goal of identifying ways of transferring the “olonkho style”, i.e. transferring the Yakut language features to the translation not only through culture-specific vocabulary but by other means as well. In result, the means of the Russian language able to adequately convey the “olonkho style” in Russian are identified. First of all, these are the tools that distinguish elevated style in the Russian language itself - archaisms and high style vocabulary. Translators choose words with the lowest level of national features from the wide range of this vocabulary, i.e. those words that are applicable to translate elevated style texts of any other language. When conveying the “olonkho style”, the morphological methods of composition and synonyms and antonyms combination in paired words are actively used. These word-building patterns are specific for the Russian language, but when translated from Yakut into Russian, the national features are conveyed by the unusual combinations of words for the Russian language. The most distinctive feature of the “olonkho style” - and the most difficult in translation - is the conveyance of the rhythmic pattern of the epic narration. This can be done by imitating syntactic parallelisms based on vowel harmony and synonymity, by constructing equal-word and parisyllabic repeating syntactic constructions that do not necessarily reproduce the number of parallelisms in the original. Thus, when translated into Russian, the “olonkho style” is recreated not only due to the exoticness of the source material but also due to the exploitation of word-building and clause-forming potential of the target language.